PERBEDAAN PERILAKU MALADAPTIF PADA ANAK USIA PRASEKOLAH DITINJAU DARI JENIS KELAMIN DAN TINGKAT PENDIDIKAN ORANG TUA - Arliska Putri Arianti; Widyastuti - (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2023)
This research is motivated by the phenomenon of maladaptive behavior in preschool children. Preschool age has an important role in preparing children to enter education. Maladaptive behavior is influenced by several factors including environmental, genetic and psychological. The study aims to determine differences in maladaptive behavior in preschool-age children in terms of gender and parental education level. This type of research is quantitative comparison. The population was 205, namely mothers who have preschool children aged 3-6 years. The sample determination used a saturated sample technique where the entire existing population was used as a research sample. The variables in this study are maladaptive behavior and demographic variables of gender and education level of parents. The research data collection technique used a maladaptive behavior scale adapted from the Strength and Difficulties Questionare (SDQ). The data analysis technique uses Regression Test with the help of JASP 16.0. The results showed that there was no significant influence between gender on maladaptive behavior that was raised (Mann-Whitney 4954.000, p = 0.495> 0.05) and there was a significant influence between the level of parental education on maladaptive behavior that was raised (Kruskal-Wallis 10.202, p = 0.001 <0.05).